A segmented capacitance tomography for visualizing material distributions in pipeline conveying crude palm oil - Mohamad, Elmy Johana (2012)
A segmented electrical capacitance tomography (ECT) imager for palm oil process monitoring system is constructed and presented in this work.The goal of this study is to use the process monitoring system as an instrument to upkeep the local and foreign palm oil mill. This is to ensure that the monitoring of crude palm oil (CPO) in conveying pipeline during extraction of palm oil mill process flow process is efficiently controlled. The system has the capability to visualize the percentage of liquid that exist within the vessel therefore the data can be utilized to design and create better process equipment in mill process. It will also be used to control some processes in order to boost the quality of crude palm oil and the POME (Palm Oil Mill Effluent) treatment process. Most ECT in earlier research were created rapidly and utilized well in multiphase flow measurement in numerous applications such as in oil and gas industries, gas/solids cyclone, milk flows and fluidized beds. Experimentally, this work investigates the capability of using a twin-plane segmented ECT sensor with 16 portable electrodes using two differential excitation potentials transmitted signal in order to recognize the concentration and velocity profile as well as the phase concentration of crude palm oil related multiphase systems (liquid and gas). The attained concentration profile which is received from the capacitance measurements is capable to provide image of the liquid and gas mixture in the pipeline therefore, the separation process (between oil and liquid waste) becomes much easier and the crude palm oil‟s quality can be dependably monitored. The visualization results deliver information regarding the flow regime, superficial velocity and concentration distribution in two-phase flow-rate measurement system incorporating a liquid flow measuring device. The information obtained is able to help in the process equipment designing, verification of existing computational modeling and simulation techniques. It may also assist in process control and monitoring during the palm oil extraction process